Investigating the Relationship between Nursing Technicians' Knowledge, Attitudes, and Practices Regarding Patient Assessment and Patient Safety Outcomes in Saudi Arabian Hospitals: A Cross-Sectional Study - Jamilah Faleh Shirshab Aljameeli,; Ghadeer Thujayl Otaysh Aldhafeeri,; Abeer Thujayl Otaysh Aldhafeeri,; Abdullah Khamais H Alshammari,; Amal Shutayt Madloul Alshammari,; Sabirin Sayer Mahdi Albanaqi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Nursing technicians play a crucial role in patient assessment and ensuring patient safety. However, limited research has explored the relationship between their knowledge, attitudes, practices regarding patient assessment and patient safety outcomes in Saudi Arabian hospitals. This study investigated this relationship and identified influencing factors. Methods: A cross-sectional study was conducted among 500 nursing technicians from 10 hospitals using convenience sampling. Data were collected via a validated questionnaire assessing knowledge, attitudes, practices, and safety outcomes. Descriptive statistics, Pearson's correlation, and multiple regression were used for analysis. Results: Participants demonstrated good knowledge (M=80%, SD=12%), positive attitudes (M=85%, SD=10%), and moderate practices (M=70%, SD=15%) regarding patient assessment. Knowledge, attitudes, and practices were significantly correlated with each other (r=0.55-0.70, p<0.001) and with safety outcomes (r=0.40-0.60, p<0.001). Regression analysis revealed that knowledge (β=0.35, p<0.01), attitudes (β=0.30, p<0.01), and practices (β=0.25, p<0.05) significantly predicted safety outcomes. Conclusion: Nursing technicians' knowledge, attitudes, and practices regarding patient assessment are interrelated and significantly influence patient safety outcomes. Targeted education, training, and policies are recommended to enhance nursing technicians' competencies and create a safety culture, ultimately improving patient safety in Saudi Arabian hospitals.